ANSWER
![x = (3)/(2) \: or \: x = - 3](https://img.qammunity.org/2020/formulas/mathematics/college/7589uwuz6qtp9nxxb8b6x66dffanke2xc0.png)
Step-by-step explanation
We want to find the roots of the parabola with equation:
![2 {x}^(2) + 5x - 9 = 2x](https://img.qammunity.org/2020/formulas/mathematics/college/d48bzhruo67gqzz1mp6xbcjdgh5tjw0gb1.png)
We need to write this in the standard quadratic equation form.
We group all terms on the left to get:
![2 {x}^(2) + 5x - 2x - 9 = 0](https://img.qammunity.org/2020/formulas/mathematics/college/lk1ww7tus8xles9drd5aow7gvyv7uz2w3v.png)
We simplify to get:
![2 {x}^(2) +3x- 9 = 0](https://img.qammunity.org/2020/formulas/mathematics/college/bxa8nscf971gui8lhrspdray5qhsh7yrwe.png)
We now compare to:
![a {x}^(2) + bx + c = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3i4p36yae7mlnttp9sryr8nhjit0psdlyi.png)
![\implies \: a = 2 , \: \: b = 3 \: \: and \: c=- 9](https://img.qammunity.org/2020/formulas/mathematics/college/36h7mczpd0rds9ucf4s71b0ohqny298lgb.png)
![\implies ac = 2 * - 9 = - 18](https://img.qammunity.org/2020/formulas/mathematics/college/jru0py7y4tscty2alufvqhc2fytcxy69hy.png)
The factors of -18 that sums up to 3 are -3, 6.
We split the middle term with these factors to get:
![2 {x}^(2) +6x - 3x- 9 = 0](https://img.qammunity.org/2020/formulas/mathematics/college/esdaqcprh2sff9i59r4yetlw0eo8imhcou.png)
Factor by grouping:
![2x(x + 3) -3(x + 3) = 0](https://img.qammunity.org/2020/formulas/mathematics/college/wh75dx1usuhxud7jaw2rtzkc89b8gd02ww.png)
Factor again to obtain:
![(2x - 3)(x + 3) = 0](https://img.qammunity.org/2020/formulas/mathematics/college/kd6f4kvdd0mm4etohx1nk8ezpo20tq0fwr.png)
Apply the zero product principle to get:
![2x - 3 = 0 \: or \: x + 3 = 0](https://img.qammunity.org/2020/formulas/mathematics/college/cn7350p5ou1bp9wwdrsa1h0lp66xlkx0ib.png)
![\implies \: x = (3)/(2) \: or \: x = - 3](https://img.qammunity.org/2020/formulas/mathematics/college/bjmtgeks3wh5apcfb5yvwkoyadvdgdij8a.png)